2012
DOI: 10.1111/j.1468-0009.2012.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure, Apology, and Offer Programs: Stakeholders’ Views of Barriers to and Strategies for Broad Implementation

Abstract: Context:The Disclosure, Apology, and Offer (DA&O) model, a response to patient injuries caused by medical care, is an innovative approach receiving national attention for its early success as an alternative to the existing inherently adversarial, inefficient, and inequitable medical liability system. Examples of DA&O programs, however, are few. Methods:Through key informant interviews, we investigated the potential for more widespread implementation of this model by provider organizations and liability insurer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 37 publications
0
56
0
4
Order By: Relevance
“…6 None protects the full scope of information that patients report needing when an unexpected outcome arises: a preliminary explanation of what happened; an expression of sympathy; an admission of responsibility; and a final analysis of the causes and consequences of the event, with information about remedial actions taken to prevent such incidents in the future. 6,29,30 In project team discussions and interviews, 19 AHRQ project participants in both New York and Massachusetts cited the absence of apology protections as a potential barrier to adopting CRPs. Although Massachusetts had protected statements of regret since the 1980s, it enacted a stronger law in 2012 after the state's CRP planning project found that stakeholders perceived this degree of protection to be insufficient.…”
Section: Type Of Reform Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 None protects the full scope of information that patients report needing when an unexpected outcome arises: a preliminary explanation of what happened; an expression of sympathy; an admission of responsibility; and a final analysis of the causes and consequences of the event, with information about remedial actions taken to prevent such incidents in the future. 6,29,30 In project team discussions and interviews, 19 AHRQ project participants in both New York and Massachusetts cited the absence of apology protections as a potential barrier to adopting CRPs. Although Massachusetts had protected statements of regret since the 1980s, it enacted a stronger law in 2012 after the state's CRP planning project found that stakeholders perceived this degree of protection to be insufficient.…”
Section: Type Of Reform Descriptionmentioning
confidence: 99%
“…25 In interviews that a group of researchers 19 conducted with stakeholders before the increase, the state's near-total charitable immunity was the most frequently mentioned barrier to the widespread adoption of CRPs.…”
Section: Type Of Reform Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Th ese included a compulsory 6-month pre-suit notice period requiring a plaintiff to provide written specifi cs of the intended claims before fi ling suit, which potentially served to facilitate collaborative claims investigation ( 6 ). A recent study examining stakeholders ' perceived barriers to implementation of DA & O programs categorized these barriers into four groups: cultural barriers such as physicians ' discomfort with disclosure and apology and fears about greater liability exposure, legal barriers such as physicians ' fears of name-based reporting of malpractice settlements and variability in governing state laws, logistical obstacles such as practice variability and complexities of inter-insurer coordination, and political barriers including ensuring favorable public policies / legislation and reassuring the public that such a system serves their best interests ( 7 ). Indeed, it is vital to recognize that a DA & O program is not, at its essence, a claims management strategy.…”
Section: Discussionmentioning
confidence: 99%